PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Sub Sektor Hotel, Restoran dan Pariwisata Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur - Ramadhan, Delia Fitri; Oktaviani, Retno Fuji (PT. Media Edutama Nusantara, 2024)
This study analyzes the association between stock prices and several financial metrics, including the present ratio, debt-to-equity ratio, net profit margin, and earnings per share. The study's population consisted of fifty enterprises from the hotel, restaurant, and tourism subsector that were listed on the Indonesia Stock Exchange between 2019 and 2023. The study's sample of seventeen firms was selected with purposive sampling technique. The inquiry covered the years 2019–2023, all included. The method of choice for the inquiry was multiple linear regression analysis in SPSS version 22. The results showed that the stock price had significant relationship with the debt-to-equity ratio and had no significant current ratio, net profit margin, or earnings per share.